What Imaging‐Detected Pathologies Are Associated With Shoulder Symptoms and Their Persistence? A Systematic Literature Review. Issue 8 (6th June 2018) - Tran, Gui; Cowling, Paul; Smith, Toby; Bury, Julie; Lucas, Adam; Barr, Andrew; Kingsbury, Sarah R.; Conaghan, Philip G.
Abstract : Objective: Shoulder symptoms are common, and imaging is being increasingly used to help with management. However, the relationship between imaging and symptoms remains unclear. This review aims to understand the relationship between imaging‐detected pathologies, symptoms, and their persistence. Methods: A systematic review using Medline, EMBASE, Cochrane, and grey literature was conducted to April 2017. The cross‐sectional and longitudinal relationships between imaging‐detected abnormalities and symptoms were analyzed and associations qualitatively characterized by a best‐evidence synthesis based on study design, covariate adjustment, and the Grade of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. Modalities included ultrasound, magnetic resonance imaging (MRI), radiographs, positron emission tomography (PET), bone scintigraphy, and computed tomography. Results: A total of 6, 569 abstracts was screened and 56 articles were included. In total, 50 studies did not adjust for covariates and 36 analyzed individual pathologies only. The majority of studies showed conflicting results. There was no significant association between most imaging features and symptoms among high‐quality, cross‐sectional studies. There was low‐quality evidence that enhancement of the joint capsule on MRI and increased uptake on PET were associated with symptoms in adhesive capsulitis. Based on high‐quality longitudinal studies, enlarging rotator cuff tears were associated with an increased incidence of symptoms. Conclusion: There were conflicting results on the association of imaging features with shoulder symptoms and their persistence. The existing evidence was very low in quality, based on the GRADE methodology. Further high‐quality studies are required to understand the relationship between imaging and shoulder symptoms and to determine the appropriate role of imaging in care pathways.